Challenges in Managing Oral Manifestations of Anticonvulsant-Induced Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome - Fajrin, Fildzah Nurul; Wardhany, Indriasti Indah; Rahmayanti, Febrina; Ikhsan, Muhammad; Pangeran, David (Odonto : Dental Journal, 2025)
Background : Antiepileptic drugs were common causative agents for DRESS syndrome, which was a severe, idiosyncratic drug hypersensitivity reaction characterized by a prolonged latency period, fever, rash, and marked eosinophilia. The oral manifestations present a diagnostic challenge due its similarity to other hypersensitivity reactions as well as its comprehensive management. Objective: This case report aims to describe the challenges in comprehensive management of DRESS syndrome severe oral manifestations, highlighting the  challenges from diagnosis to management for patient with complex comorbidities. Case: A 19-year-old female inpatient was referred to Oral Medicine division, Dental and Oro-maxillofacial unit of Universitas Indonesia Hospital  (RSUI) for severe oral sores after treated with phenytoin and lamotrigine for her temporal lobe epilepsy and bipolar affective disorder. Patient shows general weakness and clinical examination revealed multiple intra oral erosions, lips erosions with exfoliation and haemorrhagic crust, generalized maculopapular rash, facial oedema, tender lymphadenopathy, and. Laboratory findings confirmed a severe hyper-eosinophilia (32%) and lymphopenia (13.5%), while liver function was normal. A diagnosis of DRESS syndrome was finally established. Case management were immediate withdrawal of phenytoin and lamotrigine, followed by multidisciplinary care including intra vena and topical corticosteroids. The patient's condition significantly improved after collaborative comprehensive treatment. Conclusion: Definitive diagnosis decisions requires careful consideration on the correlation of clinical findings, medication history, and hallmark laboratory results, especially in patients with complex comorbidities and intraoral clinical features with characteristics similar to other hypersensitivity reactions. Comprehensive collaborative management, including patient’s and other healthcare professionals collaboration, is crucial for successful treatment.